ANALYSIS OF DIFFICULTIES IN LEARNING TO READ AND WRITE THE QUR'AN OF GRADE V STUDENTS AT MI YAKTI DLINGGO NGADIREJO MAGELANG - Ainul Hasna El khumaira; Abdul Majid; Noor Aziz (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2025)
Madrasah Ibtida'iyah Yakti Dlinggo Ngadirejo Tegalrejo Magelang is not only about learning to read and write the Quran, but also about contemplating the beauty of the meaning embedded in each letter presented. This study examines the difficulties of fifth-grade students in reading and writing the Quran at Madrasah Ibtida'iyah Yakti Dlinggo Ngadirejo Tegalrejo Magelang. The aim is to understand these problems and offer strategic solutions. The implications go beyond the school, providing relevant insights for similar educational settings. This research contributes to discussions on educational equity and inclusivity, and highlights the importance of tailored interventions to improve students' language and cultural skills.